Adult breast, lung, pancreatic, upper and lower gastrointestinal cancer patients with hospitalized venous thromboembolism in the national French hospital discharge database - F. Couturaud; I. Mahé; J. Schmidt; J-C. Gleize; T. Lafon; A. Saighi; F. Sedjelmaci; L. Bertoletti; P. Mismetti (BMC Cancer, 2023)
Abstract Background Venous thromboembolism (VTE) and cancer are strongly associated. In France, evidence on patients with pancreatic, upper GI [gastrointestinal], lower GI, lung, or breast cancer-associated VTE and their hospital management is limited. The aims of this study were to provide data on the number of hospitalized VTE events among cancer patients, the patients’ characteristics, and their hospital management to estimate the burden of disease and the hospital burden of cancer-related VTE and to provide guidance on research. Methods This longitudinal, observational, and retrospective study was based on the comprehensive hospital discharge database (PMSI). Adult patients (≥ 18 years old) hospitalized with a cancer of interest in 2016 and hospitalized (within 2 years with VTE (captured a as a principal, related, or significant associated diagnosis) were included in the study. Results We identified 340,946 cancer patients, of which 7.2% (24,433 patients) were hospitalized with VTE. The proportions of hospitalized VTE were 14.6% (3,237) for patients with pancreatic cancer, 11.2% (8,339) for lung cancer, 9.9% (2,232) for upper GI cancer, 6.7% (7,011) for lower GI cancer, and 3.1% (3,614) for breast cancer. Around two thirds of cancer patients with a hospitalized VTE had active cancer (with metastases and/or receiving chemotherapy during the six months prior to the index date): from 62% of patients with pancreatic cancer to 72% with breast cancer. Around a third of patients were admitted to the hospital through the emergency room, up to 3% of patients stayed in an intensive care unit. The average length of stay ranged from 10 (breast cancer) to 15 days (upper GI cancer). Nine (lower GI cancer) to 18% (pancreatic cancer) of patients died during the VTE hospital stay. Conclusions The burden of cancer-associated VTE is substantial, both in terms of the number of patients affected and in the hospital use. These findings offer guidance on future research on VTE prophylaxis in a very high-risk population, particularly in patients with active cancer.